Effect of Job-Insecurity, Organizational Commitment, Job Satisfaction on Turnover Intention: A Case Study of Newcomer Lecturers at Private Islamic Universities in East Java Province, Indonesia - Chalim, Asep Saifuddin (Jurnal Ilmiah Peuradeun, 2018)
This study discussed employee turnover as one of the crucial problems faced by every organization. This study sought to analyze the determinants of turnover intention, such as job insecurity, organizational commitment, and job satisfaction. The objects of this study were newcomer lecturers of private Islamic universities in East Java Province, Indonesia. To analyze the relationship among independent variables and dependent variable; this study employed a correlation path model. To build the structural formulation of the correlation path model, this study used the variance-based Structural Equation Modeling (SEM) as a Partial Least Square (PLS) analysis. The study found that job insecurity influenced job satisfaction and organizational commitment. Moreover, job satisfaction and organizational commitment had positive impacts on the turnover intention. In contrast, job insecurity did not have a direct significant impact on the turnover intention, but it had indirect effect that influences job satisfaction and organizational commitment.